2017
DOI: 10.1074/jbc.m116.767715
|View full text |Cite
|
Sign up to set email alerts
|

The Chloroplast Tubulin Homologs FtsZA and FtsZB from the Red Alga Galdieria sulphuraria Co-assemble into Dynamic Filaments

Abstract: Edited by Velia M. FowlerFtsZ is a homolog of eukaryotic tubulin and is present in almost all bacteria and many archaea, where it is the major cytoskeletal protein in the Z ring, required for cell division. Unlike some other cell organelles of prokaryotic origin, chloroplasts have retained FtsZ as an essential component of the division machinery. However, chloroplast FtsZs have been challenging to study because they are difficult to express and purify. To this end, we have used a FATT tag expression system to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 17 publications
(38 citation statements)
references
References 46 publications
4
34
0
Order By: Relevance
“…Because FtsZ1 and FtsZ2 invariably colocalize in chloroplasts Vitha et al, 2001), heteropolymers probably represent the physiologically relevant protofilament configuration in vivo. Like the bacterial proteins, FtsZ1 and FtsZ2 from higher plants possess assembly-stimulated GTPase activity (Lohse et al, 2006;Olson et al, 2010;Smith et al, 2010), as do FtsZA and FtsZB from Galdieria sulphuraria (Chen et al, 2017). In most in vitro studies, chloroplast FtsZ protofilaments associated laterally into bundles, as shown by transmission electron microscopy.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Because FtsZ1 and FtsZ2 invariably colocalize in chloroplasts Vitha et al, 2001), heteropolymers probably represent the physiologically relevant protofilament configuration in vivo. Like the bacterial proteins, FtsZ1 and FtsZ2 from higher plants possess assembly-stimulated GTPase activity (Lohse et al, 2006;Olson et al, 2010;Smith et al, 2010), as do FtsZA and FtsZB from Galdieria sulphuraria (Chen et al, 2017). In most in vitro studies, chloroplast FtsZ protofilaments associated laterally into bundles, as shown by transmission electron microscopy.…”
mentioning
confidence: 99%
“…Both proteins are widely conserved across all plants and green algae (Chloroplastida) with sequenced genomes (Miyagishima et al, 2011;Vieler et al, 2012;Grosche and Rensing, 2017), and we have shown they coassemble in heteropolymers (Olson et al, 2010;Yoshida et al, 2016). Two FtsZ families, FtsZA and FtsZB, are also present in red algae and likewise form heteropolymers (Miyagishima and Kabeya, 2010;TerBush et al, 2013;Chen et al, 2017). Cyanophora paradoxa, a glaucophyte alga, contains only a single plastidic FtsZ (Sato et al, 2005;Leger et al, 2015).…”
mentioning
confidence: 99%
“…This is suggested partly by experiments showing that coassembled GsFtsZA/GsFtsZB protofilaments were much more dynamic than GsFtsZA protofilaments in vitro (Chen et al, 2017). Additionally, mutation of a conserved residue required for GTP hydrolysis drastically reduced turnover of AtFtsZ2 and GsFtsZA homofilaments in S. pombe, as expected based on the GTPase-dependent turnover of bacterial FtsZ described above.…”
mentioning
confidence: 49%
“…Recently, FtsZA and FtsZB from the red alga Galdieria sulphuraria were also shown to copolymerize in vitro (Chen et al, 2017), indicating that FtsZ heteropolymerization is a conserved feature and may be the physiologically relevant state. Studies of FtsZ dynamics in heterologous yeast systems are beginning to provide insight into the functional significance of heteropolymerization.…”
mentioning
confidence: 99%
See 1 more Smart Citation